2023
DOI: 10.3390/horticulturae9050586
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Melatonin’s Impact on Postharvest Physiology and Quality of Fruits

Syariful Mubarok,
Erni Suminar,
Adzkia Husnul Abidat
et al.

Abstract: Fruits are important horticultural commodities because they provide nutrients that help human health. Fruits are mostly consumed as fresh products; however, there are challenges in retaining the freshness, such as the rapid ripening process that triggers fruit deterioration and reduces fruit quality and nutrient content. The postharvest quality of horticultural crops is affected by pre-and postharvest treatment. Most farmers use chemical compounds and fungicides to prevent postharvest damage; however, this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Strawberry is a horticultural crop with a short shelf life. Several methods, such as good postharvest handling, were developed to reduce strawberry postharvest loss [28][29][30]. Several studies had shown that the shelf life of strawberries could be extended by several methods, such as cooling, atmosphere modification, and coating [31].…”
Section: Discussionmentioning
confidence: 99%
“…Strawberry is a horticultural crop with a short shelf life. Several methods, such as good postharvest handling, were developed to reduce strawberry postharvest loss [28][29][30]. Several studies had shown that the shelf life of strawberries could be extended by several methods, such as cooling, atmosphere modification, and coating [31].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this statement, preharvest applications of MEL were effective on increasing yield, the content of bioactive compounds (polyphenols and anthocyanins), as has been reported for pomegranate [14,15], and enhancing the quality attributes of sweet cherries such as colour, firmness, total soluble solids (TSS) and titratable acidity (TA) [16]. As a postharvest treatment, MEL could be useful to maintain and improve the postharvest quality traits in fruit and to reduce the spoilage and decay, although different effects have been obtained depending on the fruit species [17]. In addition, MEL was also effective on increasing the content of bioactive compounds and the antioxidant activity of several fruit commodities [18] but also alleviating several abiotic stresses, the most studied being chilling injury [19].…”
Section: Introductionmentioning
confidence: 99%